To hate like this is to be happy forever : a thoroughly obsessive, intermittently uplifting and occasionally unbiased account of the Duke-North Carolina basketball rivalry /: a thoroughly obsessive, intermittently uplifting and occasionally unbiased account of the Duke-North Carolina basketball rivalry. (2009) - Unknown
No abstract available